Gendered Worlds - Aulette, Judy Root; Wittner, Judith G. (New York : Oxford University Press, USA, 2012)
"In Gendered Worlds, Second Edition, authors Judy Root Aulette and Judith Wittner use the sociological imagination to explore gender relations throughout the world. They look at how concrete forms of gender, race, class, and sexual inequality operate transnationally; examine the impact of globalization on local and everyday life experiences; and identify how local actors re-imagine social possibilities, resist injustice, and work toward change. Integrating theory with empirical studies that are of particular interest to college students--including research on violence, sports, and sexuality--the authors make gender concepts genuinely interesting and accessible. They also demonstrate how students can think critically about gender, both within and beyond the classroom. Incorporating a broad range of pedagogical features, including boxed sections and end-of-chapter sections that focus on social movements, Gendered Worlds, Second Edition, is ideal for courses in sociology of gender, sociology of sex roles, and gender studies. New to this Edition * A new concluding chapter, "Gender and Globalization," and an expanded Chapter 1 * A completely rewritten Chapter 4 featuring the most current research on gender and sexuality, particularly the gendered character of heterosexuality and heterosexual relationships * A reconceptualized Chapter 9 exploring illness as a function of a global division of labor by race, ethnicity, gender, and nation * More research on gender outside of the United States in every chapter * Additional coverage of race, intersectionality, masculinity, and transgender issues"--
Machine generated contents note: -- Chapter 1: Introduction -- Chapter 2: Bodies and Gender -- Chapter 3: Socialization and the Social Construction of Gender -- Chapter 4: Sexualities -- Chapter 5: Education -- Chapter 6: Work -- Chapter 7: Families -- Chapter 8: Violence -- Chapter 9: Gender and Race Based Illness: Diseases of the Division of Labor -- Chapter 10: Politics, Prisons, and the Military -- Chapter 11: Popular Culture, Media, and the Spectacle of Sports -- Chapter 12: Religion -- Chapter 13: Gender and Religion.
Includes bibliographical references (p. 496- 498) and index
Includes bibliographical references and index.
Keywords: Sex role; Women -- Social conditions; Feminist theory